Analysis of Mechanical Performance of Steel-Concrete Composite Girder Bridge with V-Shaped Piers. (9th November 2022) - Zeng, Yong; Li, Yongqi; Yu, Tao; Wei, Jiahao
Abstract : The steel-concrete composite girder bridge with V-shaped piers is a new type of bridge structure. It has both the unique mechanical performance of a combined continuous girder and that of a V-shaped pier bridge. At present, studies on the mechanical properties of steel main girders combined with concrete deck slabs are mainly focused on the substructure for vertical piers, but piers and girders are not solidified. However, if the V-shaped piers are cemented to the main girder, the performance of the V-shaped piers will directly affect the performance of the total superstructure. The steel main girder and concrete deck slab of a steel-composite girder are considered to be different parts of the same section. The joint section is used to simulate the changes in section stiffness of each section during the different stages of construction. In this paper, the first steel-concrete composite girder bridge with V-shaped piers is studied in detail. The effects of different influencing factors on the structural forces are investigated using finite element analysis. The results show that the force performance of this bridge type is strongly influenced by the structure. These can provide guidance for the design and construction of this bridge type, which is of great significance.